PROGRAM PASSING GRADE C++ BERBASIS KODE BLOCKS PADA PERHITUNGAN NILAI AMBANG BATAS KELULUSAN TES CPNS - Prasetyo, Andy; Sahila, Isna (STMIK Mataram, 2019)
Test for civil servant candidates (CPNS) have become paradigm for governments to recruit employes who work in various installations within the government. In 2018, the government also held a civil servant recruitment test test again. In talking issue the threshold value or passing grade on the decision usually the government passes the basic competency test (TKD). From the calculation of passing grade that fulfills the number of percentages, the CPNS test said to have passed the test. The CPNS test it self is held thoroughly to all region of Indonesia so it is only natural that the number of CPNS test participants who make so much data processing becomes completed. Not to mention the calculation of the passing grade of each participant. The passing grade algoritm uses the codeblocks based C++ langue in calculating the passing therhold value of the CPNS 2018 test so that in calculating the passing grade of each participant it self become more time efficient and guaranteed. In addition the passing grade algoritm program uses the evectivenees of the calculation result. The ceit langue based on codeblocks in calculating this there threshold value can be a reference in conducting CPNS test exercise to find out about self-forgivenes